Pediatric advanced appendicitis: open versus laparoscopic approach - Nwokoma, Ngozi Joy; Swindells, Mark G; Pahl, Karoline; Mathur, Azad B; Minocha, Ashish; Kulkarni, Milind; Tsang, Thomas (Surgical laparoscopy, endoscopy & percutaneous techniques, 2009)
Optimal surgical approach for advanced pediatric appendicectomy remains controversial. We compare the open versus the laparoscopic approach. Retrospective case notes review of children operated on for advanced appendicitis between January 2005 and July 2006 was undertaken for length of hospital stay, operating time, wound complications, need for further surgery, and hospital readmission. Forty children were included, 17 were treated with open approach and 23 with laparoscopic approach. There was no conversion from laparoscopic to open approach. Overall complication rate, length of hospital stay, and need for further surgery were similar in both groups. The mean operative time was longer in the laparoscopic group. Wound complications occurred more in the open group. Readmission for gastrointestinal obstruction was noted in the laparoscopic group. Laparoscopic approach is safe for advanced appendicitis in children. The outcomes are comparable in both study groups.